Quality of life of caregivers of children with psychiatric illnesses: a comparative study in a tertiary care hospital, Kolkata - Mitra, Sayeli; De, Rajesh; Basu, Mita; Inba Raja A,; Jadab Chandra Sardar, (Asian Journal of Medical Sciences, 2023)
Background: Childhood psychiatric morbidity is a serious issue in middle- and low-income countries. With the increasing prevalence of mental disorders among children, the role of caregivers has become vital. As a result of caregiving, caregivers experience financial difficulties, a reduction in social contact, emotional distress, and poor mental and physical health, which may lead to a low quality of life (QOL) among them. Aims and Objectives: This study aims to explore the QOL of caregivers attending the psychiatry OPD of a tertiary healthcare facility for their child’s treatment and to compare it with that of caregivers of children without psychiatric problems. Materials and Methods: A cross-sectional observational-analytical study was conducted at a tertiary care center in Kolkata. The sample size was estimated to be 75 for each group. The WHOQOL-BREF questionnaire was used for the data collection. The data were analysed using IBM SPSS version 16. Mann Whitney U test was done to compare the scores between caregiver groups. Results: The QOL scores of caregivers of children with psychiatric illnesses in different domains were physical health (11.69±1.74), psychological (9.78±2.72), social relationships (11.12±2.86), and environmental (11.66±2.13). The overall QOL of caregivers attending psychiatry outpatient departments was found to be significantly affected as compared to caregivers of children without psychiatric illnesses, except for the environment domain. Conclusion: In this study, the most affected QOL domain in the case of caregivers of children attending psychiatry OPD was the psychological domain, followed by the social relationship domain. This finding highlighted the need for socio-psychological support and a better environment for improving QOL.